2020
DOI: 10.3390/polym12040764
|View full text |Cite
|
Sign up to set email alerts
|

Design of A High Performance Zeolite/Polyimide Composite Separator for Lithium-Ion Batteries

Abstract: A zeolite/polyimide composite separator with a spongy-like structure was prepared by phase inversion methods based on heat-resistant polyimide (PI) polymer matrix and ZSM-5 zeolite filler, with the aim to improve the thermal stability and electrochemical properties of corresponding batteries. The separator exhibits enhanced thermal stability and no shrinkage up to 180 °C. The introduction of a certain number of ZSM-5 zeolites endows the composite separator with enhanced wettability and electrolyte uptake, bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…In this work we have designed the electrolyte with the addition of an inorganic water (H 2 O) and hydrogen fluoride (HF) scavenger, [23][24][25] nano H-ZSM-5 zeolite (NZeo). It consists of a framework of linked tetrahedra, each consisting of four O atoms surrounding a cation.…”
mentioning
confidence: 99%
“…In this work we have designed the electrolyte with the addition of an inorganic water (H 2 O) and hydrogen fluoride (HF) scavenger, [23][24][25] nano H-ZSM-5 zeolite (NZeo). It consists of a framework of linked tetrahedra, each consisting of four O atoms surrounding a cation.…”
mentioning
confidence: 99%
“…Table 5 showed the thermal property of PK compared with the other membranes such as PAN nanober membrane for water treatment application and PE or PP membranes for Li-ion battery application. 33,34 As a result, PK showed the similar thermal property with PAN, indicating there might be no problem at high temperature water treatment application. However, Table 5 indicated that PK had better thermal property than the commercial PE or PP battery separators.…”
Section: Resultsmentioning
confidence: 81%
“…6 Tensile strength of PK micro/nano fiber membranes. Table 5 Thermal properties of PK, PE, PP and PAN membranes (IDT: initial decomposition temperature, FDT: final decomposition temperature) 19,33,34 Sample name…”
Section: Acknowledgementsmentioning
confidence: 99%
“…A cage size of 5Å was chosen to channel the solvated sodium ions efficiently [42–45] . Zeolite‐like materials have been used in lithium‐ion batteries before as a solid electrolyte, to capture moisture, to enhance the wettability of the separator, or use of a silicon‐zeolite compound for better cycling stability [46–55] . Some patents state the use of metal composites (metal oxide and metal‐carbon alloyed), such as zeolite, within the electrode slurry for lithium‐ion batteries [56] .…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45] Zeolite-like materials have been used in lithiumion batteries before as a solid electrolyte, to capture moisture, to enhance the wettability of the separator, or use of a siliconzeolite compound for better cycling stability. [46][47][48][49][50][51][52][53][54][55] Some patents state the use of metal composites (metal oxide and metalcarbon alloyed), such as zeolite, within the electrode slurry for lithium-ion batteries. [56] Previous work has shown the benefit of nano-zeolite additives at low weight percentages in sodium-ion electrolytes.…”
Section: Introductionmentioning
confidence: 99%